2022
DOI: 10.21931/rb/2022.07.02.26
|View full text |Cite
|
Sign up to set email alerts
|

Study the quality of drinking water in the holy city of Karbala

Abstract: This study aims to assess the quality of drinking water in Karbala. Furthermore, the quality of tap and bottled water are compared in this study. Materials and method: Physical, chemical, and bacteriological parameters were all measured in the study. The bacteriological test includes a total count of coliform and fecal coliform, which may be detected using standard microbiology procedures. Results: In bottled water, total dissolved salts (TDS), Ca, Cl, and Mg were within acceptable ranges, like that in tap wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…A study conducted by 33 . indicated that social support plays an important role in healthy change, which generates in participants a love of change, leading to increased activity related to effectiveness 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by 33 . indicated that social support plays an important role in healthy change, which generates in participants a love of change, leading to increased activity related to effectiveness 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, if the pH is greater than 7.0, it is alkaline. Corrosion of metal pipes and the plumbing system can be caused by acidic water [14]. The normal drinking water pH range indicated by World Health Organization (WHO) (6.5-8.5) [15] and the Libyan National Center for Standardization and Metrology (LNCSM) (6.5-8.5) [16] (Table 13).…”
Section: Discussionmentioning
confidence: 99%

Chemical Analysis of Drink Water Samples for some Water Purification and Treatment Stations in El-Beida City - Libya and Compared with Residential and Mineral Water

طارق السيفاط محمد طيب,
جلال محمد عبد القادر المنفي,
جبريل الدايخ أصبيح الدايخ
2022
JOPAS
“…The problem of being unable to access an adequate drinking water supply is exacerbated by long periods of drought 53 . On the Galapagos Islands, of the total number of households (8,346) that have some water supply in rural areas, 17% receive water from the public water mains, while the rest collect water from wells, the rain, irrigation channels, or water delivery trucks that possibly there is bacterial contamination that exceeds the permissible limit, a scenario similar to areas far from the center of the city of Karbala (Iraq), where bottled water is contaminated 54 . To avoid problems related to water stress and public health, it is essential to use a natural carbon filter and solar disinfection as alternatives for more significant removal of contaminants [51][52][53] .…”
Section: Table 3 Housing Typology By Sector On the Galapagos Islands ...mentioning
confidence: 99%